2002
DOI: 10.1023/a:1025383913444
|View full text |Cite
|
Sign up to set email alerts
|

The role of decorin in collagen fibrillogenesis and skin homeostasis

Abstract: Decorin, a prototype member of the growing family of the small leucine-rich proteoglycans (SLRP's), plays significant roles in tissue development and assembly, as well as playing both direct and indirect signaling roles. This review will concentrate on decorin's function in collagen fibrillogenesis as determined through the study of mice with a disrupted decorin gene. The fragile skin and abnormal tendon phenotypes initially observed were found to be due to fundamental alterations in collagen fibers, highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
268
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(287 citation statements)
references
References 55 publications
11
268
0
Order By: Relevance
“…The importance of SLRPs in regulating fibrillogenesis has become clear from studies of SLRP-deficient mice (32)(33)(34)(35)(36), some of which have phenotypes resembling EDS. However, thus far no mutations have been identified in any of the SLRPs in HT-EDS or BJHS.…”
Section: Genetics Of Ht-eds and Bjhsmentioning
confidence: 99%
“…The importance of SLRPs in regulating fibrillogenesis has become clear from studies of SLRP-deficient mice (32)(33)(34)(35)(36), some of which have phenotypes resembling EDS. However, thus far no mutations have been identified in any of the SLRPs in HT-EDS or BJHS.…”
Section: Genetics Of Ht-eds and Bjhsmentioning
confidence: 99%
“…Decorin is ubiquitous in tendon and is regularly attached to the surface of collagen fibrils (Cribb and Scott, 1995;Raspanti et al, 1997) (see also, Figure 1). Decorin has been identified as a critical factor in the structural organization and development of the tissue (Birk et al, 1995;Reed and Iozzo, 2002;Zhang et al, 2006) as well as a promoter of nutrient diffusion (Koob and Summers, 2002). In addition to aiding in the bearing of compressive loads (as hydrophilic molecules that attract water), it has also been suggested that decorin may play a direct role in the support of tensile loads (Cribb and Scott, 1995;Hedbom and Heinegard, 1993;Korhonen et al, 2003;Liao and Vesely, 2007;Robinson et al, 2005;Robinson et al, 2004;Ruggeri A., 1984;Scott, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Decorin is an abundant proteoglycan in the tendon matrix and is a well-studied proteoglycan for loaded tendons. 6,7 Increasing the production of type I collagen and decorin may enhance tendon healing.…”
mentioning
confidence: 99%